Harald Szeemann : individual methodology - Derieux, Florence (Zürich : JRP/Ringier Kunstverlag Ag, 2007)
Aubart, Francois ; Cistiakova, Julija ; Kim, Haeju ; Pasapane, Lucia ; Pinaroli, Fabien ; Roalandini Beyer, Karla Gabriela ; Tokuyama, Yuka ; Woods, Sadie
CCS Gent
boek
Keywords: Szeemann, Harald